Lower Limb Exoskeleton Sensors: State-of-the-Art - Neťuková, Slávka; Bejtic, Martin; Malá, Christiane; Horáková, Lucie; Kutílek, Patrik; Kauler, Jan; Krupička, Radim (Sensors (Basel, Switzerland), 2022)
Due to the ever-increasing proportion of older people in the total population and the growing awareness of the importance of protecting workers against physical overload during long-time hard work, the idea of supporting exoskeletons progressed from high-tech fiction to almost commercialized products within the last six decades. Sensors, as part of the perception layer, play a crucial role in enhancing the functionality of exoskeletons by providing as accurate real-time data as possible to generate reliable input data for the control layer. The result of the processed sensor data is the information about current limb position, movement intension, and needed support. With the help of this review article, we want to clarify which criteria for sensors used in exoskeletons are important and how standard sensor types, such as kinematic and kinetic sensors, are used in lower limb exoskeletons. We also want to outline the possibilities and limitations of special medical signal sensors detecting, e.g., brain or muscle signals to improve data perception at the human-machine interface. A topic-based literature and product research was done to gain the best possible overview of the newest developments, research results, and products in the field. The paper provides an extensive overview of sensor criteria that need to be considered for the use of sensors in exoskeletons, as well as a collection of sensors and their placement used in current exoskeleton products. Additionally, the article points out several types of sensors detecting physiological or environmental signals that might be beneficial for future exoskeleton developments.
Keywords: sensors; dolní končetina; Movement; exoskeleton; Aged; wearable robots; Lower Extremity; pohyb; biomechanika; Humans; senioři; lidé; Biomechanical Phenomena; lower limbs; Exoskeleton Device; powered orthosis; exoskeletons